2021
DOI: 10.1002/prot.26065
|View full text |Cite
|
Sign up to set email alerts
|

Deep learning pan‐specific model for interpretable MHC‐I peptide binding prediction with improved attention mechanism

Abstract: Accurate prediction of peptide binding affinity to the major histocompatibility complex (MHC) proteins has the potential to design better therapeutic vaccines. Previous work has shown that pan-specific prediction algorithms can achieve better prediction performance than other approaches. However, most of the top algorithms are neural networks based black box models. Here, we propose DeepAttentionPan, an improved pan-specific model, based on convolutional neural networks and attention mechanisms for more flexib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(20 citation statements)
references
References 32 publications
1
19
0
Order By: Relevance
“…This pattern is in congruence with the experimental data for the binding of A*11:01 (49). Jin et al (28) reported anchor sites for MHC alleles from attention-based models. PoSHAP analysis matched these anchor sites based on the PoSHAP heatmap (Figure 4A) and the range of the SHAP values per position (Supplemental Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This pattern is in congruence with the experimental data for the binding of A*11:01 (49). Jin et al (28) reported anchor sites for MHC alleles from attention-based models. PoSHAP analysis matched these anchor sites based on the PoSHAP heatmap (Figure 4A) and the range of the SHAP values per position (Supplemental Figure 5).…”
Section: Resultsmentioning
confidence: 99%
“…All three of these have significantly greater SHAP contributions when lysine is at position nine. This may reflect that there is some flexibility with the earlier root site when lysine is bound, and may demonstrate that the model had learned the length of the binding motif between the second position and the C-terminus (28) (Supplemental Table 2, Supplemental Figure 5).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Both classification and regression models are used to learn which peptides bind to each MHC allele, for example see O'Donnell et al, Zeng and Gifford, and Liu et al [28][29][30] However, because many reports forgo model interpretation, the learned biochemical relationships remain unknown. Other works determine relationships learned by their model, for instance both Jin et al [31], and Hu et al [32] used CNNs with an attention mechanism to determine the weights of the inputs on the final prediction.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study [33] of protein language models has shown that the output attentions of BERT-based protein models can capture biologically relevant protein properties. An attention-based deep learning model for peptide-MHC-I binding predictions [34] has shown that the attentions learned by the predictive model can capture critical amino acid positions of the peptides, which help stabilize the peptide-MHC-I bindings.…”
Section: Introductionmentioning
confidence: 99%